Emily's Multimodal Hallucination Experience in Alexandra Potter's Me and Mr. Darcy - Agustin, Nanda Friska Tiya; Prasaja, Y. B. Agung (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
This article examines Emily's multimodal experiences in Alexandra Potter's Me and Mr. Darcy with a focus on its relationship to the phenomenon of hallucinations. Hallucination is described as an incorrect sensory experience in which an individual perceives sights, odors, flavors, textures, or sounds that are not present in reality. In term of hallucination, multimodal is a type of hallucination that is a mixture of various sensory modalities, creating the perception that they originate from a single source. This article seeks to explore the types of various sensory modalities that constitute Emily's multimodal hallucination experience. This article employs a qualitative analysis method to explore an in-depth examination of the various sensory modalities of Emily’s hallucination. A psychological approach is used in this article to uncover Emily’s hallucination. This analysis utilizes Veague's theory about the forms of hallucination. The analysis shows that Emily experiences multimodal hallucination which is a combination of visual, auditory, tactile, olfactory, and gustatory hallucination that makes her feel that she can see the physical form, hear the voice, feel the touch, taste the food, and smell Mr. Darcy's perfume. The combination of these several sensory modalities that occur simultaneously makes the existence of Mr. Darcy seem real to Emily. Keywords: hallucination, multimodal, sensory experience